2015
DOI: 10.1111/andr.12098
|View full text |Cite
|
Sign up to set email alerts
|

Isolated abnormal strict morphology is not a contraindication for intrauterine insemination

Abstract: SUMMARYThis study sought to investigate whether isolated abnormal strict morphology (<5% normal forms) and very low strict morphology (0-1% normal forms) affects pregnancy rates in intrauterine insemination (IUI). This was a retrospective study performed at an Academic Medical Center/Reproductive Medicine Center. Four hundred and eight couples were included for 856 IUI cycles. 70 IUI cycles were performed in couples with abnormal strict morphology and otherwise normal semen parameters. Outcomes were measured a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 38 publications
(51 reference statements)
0
12
0
Order By: Relevance
“…However, this limitation is alleviated by the lack of strong correlation between teratozoospermia and reduced ICSI outcomes. 60 According to Lockwood et al, 61 teratozoospermia should not be relevant when choosing IVF technique. In fact, even intrauterine inseminations are successful for teratozoospermic patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, this limitation is alleviated by the lack of strong correlation between teratozoospermia and reduced ICSI outcomes. 60 According to Lockwood et al, 61 teratozoospermia should not be relevant when choosing IVF technique. In fact, even intrauterine inseminations are successful for teratozoospermic patients.…”
Section: Discussionmentioning
confidence: 99%
“…Zhu et al [14] suggested that isolated teratozoospermia (<4% of normal forms according to the Kruger’s classification [15]) justifies the use of ICSI versus IVF to improve the fertilization rate. Conversely, according to Lockwood et al [16], teratozoospermia is not a parameter to be taken into account for the choice of ART technique and allows even intra-uterine inseminations. These results confirm those reported by Fan et al [17].…”
Section: Discussionmentioning
confidence: 99%
“…In a meta-analysis (43), the threshold values showing an impact of sperm morphology on pregnancy rates were 4% in most cases when strict criteria were used, and varied from 8% (44) to 50% (45) when the WHO (1987,1992) criteria were used. Recent publications have failed to demonstrate a statistically significant difference in pregnancy rates in IUI cycles between groups with or without teratozoospermia (9,46).…”
Section: Figurementioning
confidence: 94%